2013
DOI: 10.21829/azm.2013.291398
|View full text |Cite
|
Sign up to set email alerts
|

Nuevos registros geográficos y notas de infección de Triatoma gerstaeckeri (Stål) y Triatoma rubida (Uhler) (Hemiptera: Reduviidae: Triatominae) en Nuevo León y Coahuila, México

Abstract: Nuevos registros geográfiCos y Notas de iNfeCCióN de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…Studies conducted in Nuevo Leon, a Mexican State next to Coahuila, reported T. cruzi infection in collected domestic and wild Triatoma gerstaeckeri made in municipality of General Teran 23 , 26 . A recent study carried out by our research group, reported the presence of native triatomines T. gerstaeckeri and T. rubida in the north of Coahuila near to the coal region, which may represent another risk factor for local Chagas disease infection 25 .…”
Section: Discussionmentioning
confidence: 83%
“…Studies conducted in Nuevo Leon, a Mexican State next to Coahuila, reported T. cruzi infection in collected domestic and wild Triatoma gerstaeckeri made in municipality of General Teran 23 , 26 . A recent study carried out by our research group, reported the presence of native triatomines T. gerstaeckeri and T. rubida in the north of Coahuila near to the coal region, which may represent another risk factor for local Chagas disease infection 25 .…”
Section: Discussionmentioning
confidence: 83%
“…Los hallazgos en el presente estudio concuerdan con lo reportado en otros autores (Salazar et al, 2010), en relación a que T. dimidiata se distribuye en el intradomicilio y el peridomicilio, en tanto que T. mexicana lo hace en el peridomicilio. T. gerstaeckeri, una especie que normalmente ha sido reportada en los tres ciclos de transmisión de T. cruzi (Martínez -Tovar et al, 2013), se encontró tanto en el peridomicilio como en el intradomicilio, en los municipios de Capulhuacan y Tianguistengo, lo que puede indicar que esta especie se está adaptando al nicho ecológico doméstico en las zonas mencionadas, lo cual podría representar un mayor riesgo de salud para la población humana.…”
Section: Detección De T Cruzi En Triatominos Mediante Pcr Múltiplexunclassified
“…Recent cases of Chagas have been reported in Coahuila ( 289 , 290 ) where T. cruzi infection has been found also in blood donors ( 290 ). There have been new records of T. gerstaeckeri and T. rubida in Nuevo Leon and Coahuila ( 291 ). As in the US, T. cruzi is increasingly transmitted through blood transfusions partly due to migration from rural areas toward Mexico City ( 292 ).…”
Section: Zoonotic Infectious Diseasesmentioning
confidence: 99%